Proceedings of the 23rd Spring Conference on Computer Graphics 2007
DOI: 10.1145/2614348.2614369
|View full text |Cite
|
Sign up to set email alerts
|

Selective rendering in a multi-modal environment

Abstract: Visual perception is becoming increasingly important in computer graphics. Research on human visual perception has led to the development of perception driven computer graphics techniques, where knowledge of the human visual system and, in particular, its weaknesses are exploited when rendering and displaying 3D graphics. It is well known that many sensory stimuli, including smell, may influence the amount of cognitive resources available to a viewer to perform a visual task. In this paper we investigate the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…Cross-modal effects refer to the impact on the perceptual experience of one sensory input that the presentation of an additional sensory input can have [19]. Previous work has demonstrated that cross-modal effects can be considerable to the extent that large amounts of detail of one sense may be ignored in the presence of other sensory inputs (see [18] and [20], and for a more recent summary see also [21]). …”
Section: Sound and Multimodal Interactionsmentioning
confidence: 99%
“…Cross-modal effects refer to the impact on the perceptual experience of one sensory input that the presentation of an additional sensory input can have [19]. Previous work has demonstrated that cross-modal effects can be considerable to the extent that large amounts of detail of one sense may be ignored in the presence of other sensory inputs (see [18] and [20], and for a more recent summary see also [21]). …”
Section: Sound and Multimodal Interactionsmentioning
confidence: 99%
“…In 2007, Ramic et al [2006] showed that smell, in their case perfume, can be used to direct a viewer's attention to the smell origin in the scene, a bowl of flowers. The area around the bowl of flowers was rendered at the highest quality, while it was possible to render the remainder of the scene at a much lower quality, and thus at a reduced computational cost, without the viewer being aware of this quality difference.…”
Section: Cross-modal Renderingmentioning
confidence: 99%
“…Knowledge of how our eyes might view a scene when more than one sense is present has been exploited in computer graphics to selectively render images at a computationally lower cost without the viewer being aware of any drop in perceived quality [Ramic et al 2006], [Mastoropoulou et al 2005a], [Ellis and Chalmers 2006]. Smell, or olfaction is a key human sense.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work [Ramic et al 2006;Brkic et al 2009] and a pilot study tested the perceived visual quality for each stimuli independently. The results showed that strong smell, high temperature and noise resulted in the lowest threshold for perceived visual quality.…”
Section: Methodsmentioning
confidence: 99%